Pengaruh Pendidikan Kesehatan dengan Metode Audio Visual terhadap Pengetahuan dan Sikap Santri dalam Pencegahan Kejadian Skabies di Pondok Pesantren Al Mawardi Desa Pasanggar Kabupaten Pamekasan - Rohman, Abd .; Rahman, Handono Fatkhur; Junnatul, Maulidiyah Azizah Junnatul (Universitas Nurul Jadid, 2023)
AbstrakIntroduction: Scabies is a significant world health problem in school or boarding children caused by Sarcotes scabiei, with dangerous systemic complications and an increased risk of death due to low priority for treatment and management. Health education with the right audio-visual method can increase one's knowledge and attitude towards a disease. Health education using the audio-visual method at Al Mawardi Islamic Boarding School aims to increase students' knowledge about scabies so that it can influence students' attitudes to adopt a healthy lifestyle so as to be able to prevent scabies.Method: The research design used a Quasi Experimental Design with a Pretest-Posttest Control Group approach and the sample was taken using a total sampling technique. This data analysis uses the Wilcoxon test and the Mann Withney test. Results: The results of the Wilcoxon test on students' knowledge showed a difference in P-value. In the experimental group, the results were P=0.000<a=0.05, while in the control group, the results were P=0.429>a=0.05. The results of the Wilcoxon test on students' attitudes in the experimental group the results were P=0.000, <a=0.05, while in the control group the results were P=0.613,>a=0.05. Conclusion: There was an influence on the knowledge and attitudes of students in preventing scabies in the experimental group. Whereas in the control group there were no significant changes before and after being given the pretest and posttest.Keywords: Health education, Knowledge and attitude, Scabies